2001
DOI: 10.1001/jama.286.24.3106
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Human Papillomavirus Infection as a Predictor of Cervical Intraepithelial Neoplasia

Abstract: A strong relationship exists between persistent HPV infections and SIL incidence, particularly for HPV types 16 and 18.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
310
4
33

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 492 publications
(362 citation statements)
references
References 22 publications
15
310
4
33
Order By: Relevance
“…Persistent HPV infection is identified by a patient having more than one positive test for the same high-risk HPV type, but repeated type-specific HPV testing would be too cumbersome to apply in clinical practice and may not distinguish persistent infection from reinfection. 3 Expression of p16 INK4a may provide a surrogate marker for persistent HPV infection. Recently, we compared p16 INK4a immunostaining with Hybrid Capture high-risk HPV DNA testing using liquidbased cytology and found that 16 INK4a immunostaining detected high-grade CIN better than the HPV DNA testing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Persistent HPV infection is identified by a patient having more than one positive test for the same high-risk HPV type, but repeated type-specific HPV testing would be too cumbersome to apply in clinical practice and may not distinguish persistent infection from reinfection. 3 Expression of p16 INK4a may provide a surrogate marker for persistent HPV infection. Recently, we compared p16 INK4a immunostaining with Hybrid Capture high-risk HPV DNA testing using liquidbased cytology and found that 16 INK4a immunostaining detected high-grade CIN better than the HPV DNA testing.…”
Section: Discussionmentioning
confidence: 99%
“…9-11 It was the repeated positive high-risk HPV test results, reflecting persistent infection that predicted a likelihood of having a high-grade CIN. 3,9 In susceptible adolescents, either repeated exposure or an inability to suppress immunologically an infection may promote the oncogenic potential of …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 The LudwigMcGill cohort 10 involved 2528 women who were followed prospectively for evidence of HPV infection using polymerase chain reaction (PCR) detection. The group was comprised of a high-risk population of women from Sao Paulo, Brazil, who attended a maternal and child health clinic.…”
mentioning
confidence: 99%